FAKTOR-FAKTOR YANG MEMPENGARUHI PENGUNGKAPAN INTELLECTUAL CAPITAL - Oktavianti, Heni (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2014)
This main aims of this study is to test whether the corporate governance mechanism whichconsists of institutional ownership, managerial ownership, the proportion of independent board ofdirectors and audit committees affect the firm value, where the quality of earnings as an interveningvariable. The research samples are Manufacturer Company which is listed in Indonesia StockExchange (IDX). The samples used are 122 companies and they are selected by purposive sampling.The statistic method is using Multiple Linear Regression Analysis, with the goodness of fit model(Goodness) and partial test (t Test). The results of this study show that: (1) corporate governance doesnot affect the quality of earnings, (2) the quality of earnings has no effect on the firm value, (3)institutional ownership effect on the firm value, and (4) the quality of earnings is not an interveningvariable in relation to the mechanism corporate governance to firm value.Keywords: Companyâs Size, Companyâs Age, Leverage, Profitability Level, IndependentCommissioners, Ownership Concentration and Intellectual Capital Disclosure.